The Role of IT Applications on New Product Performance in the Digital Age: The Role of Supply Chain Synergy Mediation - Chen, Shi (International Journal of Accounting and Financial Reporting, 2023)
Based on resource-based theory, dynamic capability theory and transaction cost theory, this paper analyzes the influence of IT application based on big data analysis on new product performance, the mediating role of supply chain collaboration and the moderating role of relationship risk between supply chain collaboration and new product performance in the context of supply chain collaboration in the digital age. The results show that IT advancement and IT consistency have significant positive effects on new product performance; Joint problem solving and information sharing in supply chain collaboration play a partial mediating role in the relationship between IT advancements and new product performance. At the same time, IT also plays a part of mediating role in the relationship between IT consistency and new product performance. Relationship risk positively moderates the relationship between information sharing and new product performance. The research conclusions not only enrich the existing theories, but also have important reference significance for the digitization and information construction and innovation development in the context of enterprise supply chain collaboration.